Tinjauan Ketepatan Kode Diagnosis Bronchitis di Unit Rawat Jalan Rumah Sakit Islam Sukapura - Muhamad Sadikin; Muhammad Rezal; Dina Sonia; Muhammad Iqbal (Yayasan Literasi Sains Indonesia, 2024)
Bronchitis is an inflammation of the bronchioles, bronchus and trachea due to various causes. The purpose of this study was to identify the accuracy of the bronchitis diagnosis code in the outpatient unit of the Sukapura Islamic Hospital. The research method used is descriptive research, namely identifying and explaining the results obtained in full regarding the accuracy of the bronchitis diagnosis code in the outpatient unit of the Sukapura Islamic Hospital. The collection technique used an observation instrument. The results of the study obtained 60 medical records of outpatient bronchitis disease diagnoses in 2023 at the Sukapura Islamic Hospital, obtained an accuracy of 36 (60%) and inaccuracy of 24 (40%) in coding, the location of the inaccuracy is divided into three classifications, namely Bronchitis Unspecified Inappropriate age of 7 (29%), errors in the category of 12 (50%) and errors in the subcategory of 5 (21%). The Standard Operating Procedure (SOP) in coding has been socialized and has been running but has not been carried out optimally because inaccuracies are still found in the coding of bronchitis disease. The SOP is still very simple and has not been revised again so it cannot be a good reference in coding disease diagnoses. It is better for coding officers to read all supporting information on the form sheet in the medical resume, in order to produce the right and specific code. And to minimize inaccuracy in coding bronchitis diagnoses, it is recommended for coding officers to re-check using ICD-volume 1.